Interactive Animated Video Oriented to a Contextual Approach to Improve Science Learning Outcomes of Grade III Students - Elsa Claudia Lippi; Nyoman Jampel; Dewa Gede Agus Putra Prabawa (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of students in the subject of Natural and Social Sciences (IPAS) remain a fundamental issue, primarily due to the limited availability of engaging learning media that are relevant to students’ characteristics. In addition, the predominantly conventional learning approaches make students less actively involved and struggle to understand contextual concepts. This study aims to develop and examine the effectiveness of interactive animation videos oriented toward a contextual approach in improving the IPAS learning outcomes of third-grade elementary school students. The type of research employed is development research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 3 students for individual trials, 9 students for small group trials, and 30 students for field trials. Data were collected through questionnaires and tests, then analyzed using quantitative descriptive techniques and inferential t-tests. The results showed that the use of contextual-oriented interactive animation videos significantly improved student engagement, understanding, and learning outcomes. The conclusion of this study emphasizes that contextual-based interactive animation video media are effective as an alternative innovative learning strategy to optimize student competencies at the elementary school level. The implication of this study is that the use of adaptive digital media can serve as a strategic solution to support 21st-century learning.